Centrumok és perifériák : Dunaújváros kulturális intézményrendszerének helye a megyei jogú városok között - Varga, Anita (Közép-Európai Közlemények, 2012)
From the beginning of the XXI. century, the operation of the institutions is getting to be harder, the attendance is getting to be lower. This fact is certified by numeral datas. The statistical analyses are confined to the operational datas of the cultural institutions. In the course of the preparing the complex analysis was important to consider that the datas - given by the Hungarian Central Statistic Office – didn’t provide comprehensive informations about the attendance, status and relations of the cultural institutions. Despite of the wrong tendency of the external circumstances - according to their possibilities - the institutes calculate with the demand of the users. It is important to maintain and preserve the operability of the cultural institutes in Dunaújváros, because the closing any of them would give an incorrigible deficit in the life of the city. The parts of the system operate properly and independently. After the economic alteration happened a significant realignment in the cultural sector, the trift became the main principle.